1998
DOI: 10.1002/(sici)1520-6408(1998)22:4<321::aid-dvg3>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking Bmp6 function

Abstract: Bmp6, a member of the 60A subgroup of bone morphogenetic proteins (BMPs), is expressed in diverse sites in the developing mouse embryo from preimplantation stages onwards. To evaluate roles for Bmp6 signaling in vivo, gene targeting was used to generate a null mutation at the Bmp6 locus. The resulting Bmp6 mutant mice are viable and fertile, and show no overt defects in tissues known to express Bmp6 mRNA. The skeletal elements of newborn and adult mutants are indistinguishable from wild-type. However, careful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
160
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(171 citation statements)
references
References 0 publications
10
160
0
1
Order By: Relevance
“…The results suggest that the response of ADAS cells to known chondrogenic agents differs considerably from the response of other mesenchyme-derived progenitor cells, such as MSCs. Notably, and in contrast to the osteogenic effects of BMP-6 on many cell types (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), the effects of BMP-6 on ADAS cells in 3-D culture are highly chondrogenic, and among the growth factors investigated in this study, BMP-6 was shown to be the most potent regulator of chondrogenesis.…”
Section: Discussionmentioning
confidence: 63%
“…The results suggest that the response of ADAS cells to known chondrogenic agents differs considerably from the response of other mesenchyme-derived progenitor cells, such as MSCs. Notably, and in contrast to the osteogenic effects of BMP-6 on many cell types (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), the effects of BMP-6 on ADAS cells in 3-D culture are highly chondrogenic, and among the growth factors investigated in this study, BMP-6 was shown to be the most potent regulator of chondrogenesis.…”
Section: Discussionmentioning
confidence: 63%
“…74 Its expression during embryogenesis is closely coupled with BMP-2, and the lack of noticeable defects in BMP-6-deficient mice may be due to functional compensation by BMP-2. 74 Nevertheless, our findings corroborate well with a recent study in which BMP-6 was shown to induce the most rapid tissue calcification when compared with BMP-2 or BMP-4 in an athymic nude rat model, 75 although for reasons to be determined AdBMP-4 reproducibly failed to induce orthotopic bone formation in this study. BMP-9 is one of the least studied members of the BMP family.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Bmp6 Ϫ/Ϫ animals survive to adulthood (Solloway et al, 1998), with no apparent fertility phenotype, despite the expression of Bmp6 in the neonatal testis (www.ncbi.gov/geo/GDS2098, GDS401, GDS605). BMP6 may be dispensable or alternatively, other BMPs may compensate for the loss of BMP6 by activating SMAD proteins to sufficient levels to induce expression of BMP6 target Diagrammatic representation of Smad1,5,8,Smad4, and Smad6 and 7 mRNA expression during adult mouse spermatogenesis based on the data described in this study.…”
Section: Discussionmentioning
confidence: 99%